Effects of Village Education and Access to Information on Mangrove Forest Areas: Studies in Indonesia - Itfan Itfan (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
This study seeks to gather empirical evidence regarding education and access to information in affecting mangrove forests in Indonesia. The motivation for this study comes from the fact that Indonesia has experienced enormous mangrove deforestation in the last three decades. This study uses village level data in Indonesia. With a combination of geospatial data and PODES, the author uses the unbalanced panel data and Fixed Effects Model (FEM) to analyze the correlation of 9-year basic education facilities and higher education as well as national private TV broadcasts and overseas TV broadcasts on the area of mangrove forests. The author found that villages that have higher education facilities and get overseas TV broadcasts have a positive correlation with the area of mangrove forests in the village area. Higher education and broad access to information globally can certainly increase villagers’ knowledge and concern about the importance of mangrove forests. Therefore, government policies are needed to improve higher education facilities and access to global information in villages to reduce the exploitation of villagers against mangrove forests, especially for village communities located around mangrove forests.